Multi‐Timescale Analysis of Tidal Variability in the Indian Ocean Using Ensemble Empirical Mode Decomposition. Issue 12 (18th December 2020) - Devlin, Adam T.; Pan, Jiayi; Lin, Hui
Abstract: Ocean tides have been observed to be changing worldwide for nonastronomical reasons, which can combine with rising mean sea level (MSL) to increase the long‐term impact to coastal regions. Tides can also exhibit variability at shorter timescales, which may be correlated with short‐term variability in MSL. This short‐term coupling may yield higher peak water levels and increased impacts of exceedance events that may be equally significant as long‐term sea level rise. Previous studies employed the tidal anomaly correlation (TAC) method to quantify the sensitivity of tides to MSL fluctuations at long‐period (>20 years) tide gauges in basin‐scale surveys of the Pacific and Atlantic Ocean, finding that TACs exist at most locations. The Indian Ocean also experiences significant sea level rise and tidal variability yet has been less studied due to a sparse network of tide gauges. However, since the beginning of the 21st century, more tide gauges have been established in a wider geographical range, bringing the possibility of better estimates of tidal and MSL variability. Here, we improve the TAC approach, using the ensemble empirical mode decomposition (EEMD) method to analyze tidal amplitudes and sea level at multiple frequency bands, allowing a more effective use of shorter record tide gauges and better understanding of multiple timescales of tidal variability. We apply this approach to 73 tide gauges in the Indian Ocean to better quantify tidal variability in these under‐studied regions, finding that the majority of locations exhibit significant correlations of tides and MSL. Plain Language Summary: The long‐term evolution of tides occurs alongside the long‐term rise in sea level, which has implications for the future of coastal communities. In addition, many locations show a short‐term correlation between mean sea level (MSL) and tides, which may amplify total water levels, and lead to short‐term flooding and inundation. The method of analyzing the correlations of MSL and tides ("tidal anomaly correlations, " or TACs) has been employed in recent studies that analyzed Pacific and Atlantic Ocean data, with the majority of locations revealing significant correlations. This study modifies previous methods to analyze tide gauges in the Indian Ocean, which has classically been understudied due to a shortfall of useable data where many tide gauges are of short record. The new approach can isolate different forms of variability from a tide gauge (e.g., seasonal, yearly, and multiyear) and allow a separate analysis via the TAC method. This approach is applied to 73 locations in the Indian Ocean to show that most exhibit significant correlation of MSL to tides at multiple time scales. The results of this study will help to better understand the nature of tidal evolution under future scenarios of sea level rise and will help coastal planning. Key Points: Tidal variability can be correlated to sea level variability in the Indian Ocean at multiple timescales Ensemble empirical mode decomposition can assist in the analysis of sparse‐record tide gauges Improved diagnosis of tidal evolution and rising sea levels in this region is essential to future coastal planning and logistics